ANALISIS DAMPAK PELAKSANAAN PROGRAM AGRIBISNIS PETERNAKAN SAPI POTONG TERHADAP PEMBERDAYAAN MASYARAKAT PEDESAAN - Zulkifli Zulkifli (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2018)
Sragen regency is one of the districts that most of the population is farmers, this research sees the impact of livestock agribusiness programs on empowerment of rural communities. The results showed that the formation of beef cattle group as much as 72.55% influenced by agribusiness programs and 27.45 livestock % formed before any program. The number of livestock cattle ownership during this activity increased by an average of 50.71%, ie 1.78 birds. the group receiving further assistance experienced a decrease of 72.55% ie 37 farmers. The level of empowerment of farmers in accessing capital from the government is 58.82%, from Bank BRI, 41.18% from Central Java Bank, 7.84% from Jamsostek and 7.84% from Balitbang 3.92%. Empowerment in accessing Market information, as much as 52.95% accessing from beauty and 47.05% accessing from the cattle market. The drug information as a whole is accessible from the government. Empowerment of farmers in accessing technology as a whole access from the government. Farmer participation through intensity level of group meeting, 80,39% meeting once a month, 5.88% 2 times in one month, 7.84% 1 time in 2 months and 5.88% 1 time in 3 months .